Discussion on the production mechanism of deep coalbed methane in the eastern margin of the Ordos Basin - Lizhu Yu; Dameng Wang; Xin Feng; Xianfeng Gu; Ming Chen; Xiaolei Wu; Jintao Kong (Energy Exploration & Exploitation)
This study builds upon the research progress in the theories of CBM desorption, diffusion, and seepage flow to explore the production mechanisms of deep coalbed methane (CBM) in the Daing-Jixian block, aiming to achieve scientific and reasonable control of gas wells. Theoretical analysis suggests that CBM adsorption belongs to liquid–solid interfacial adsorption, encompassing four stages: liquid phase adsorption—liquid phase desorption—composite desorption—gas phase desorption. Most of the desorbed gas is driven by a pressure differential in a Darcy's flow process. By calculating the Knudsen number (Kn) under various temperature, pressure, and fracture diameter conditions, the flow state can be identified. Whole-diameter CT scanning reveals a multi-scale pore-fracture system ranging from millimeters to micrometers to nanometers. Calculations show that during the gas well drainage and depressurization process, fractures of millimeter scale and larger exhibit Darcy's flow, while micron-scale fractures maintain Darcy's flow status above a reservoir pressure of 5 MPa; other scales primarily exhibit non-Darcy flow without significant macroscopic movement. In summary, starting from the fundamental mechanisms of the original multiscale tri-level pore-permeability system of the coal reservoir, through the post-fracturing transformation forming three diversion zones of high, medium, and low conductive regions, and transitioning from primarily free gas to desorbed gas in three production stages, an ideal comprehensive production model schematic for the study area has been established, providing theoretical support for on-site production management.